A review of Flow Injection Analysis Atomic Absorption SpectrometryHyphenated Systems (part II) - Jasim, Fadhil; Ali, Fatima (Iraqi Journal of Science, 2025)
This paper present a general review for chemical literature concerning the hybratilised (PIA-AAS) system scanned over the years late 1995 to late 2002 and including lots of technical innovation and developments of the this coupled system which typically utilisese the adequate precision, sensitivity and specificity (AAS) on one hand and simplicity high sample through put and economy of (FIA) on the other hand. It is worth mentioniny that a relatively large percent of persent publication of the system were abstracted from INTERNET